PERAN MODEL PENERIMAAN TEKNOLOGI, LITERASI DIGITAL DAN PROMOSI SOSIAL MEDIA DALAM MENINGKATKAN KESADARAN DALAM MEMBAYAR ZAKAT SECARA ONLINE - Jamaludin, Nur; Soleha, Aprilia Dewi (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2022)
This study aims to determine the effect of technology acceptance, promotion and digital literacy models on muzzaki's decision to pay zakat online. The sample of this research is muzzaki, Cipondoh District, Tangerang City, who already work or have income. The analytical technique used in this research is descriptive quantitative by using analysis technique Partial Least Square (PLS) or Smart PLS Version 3.0. The method used in this study is a quantitative method with the research instrument in the form of a questionnaire. Respondents in this study amounted to 80 people who were determined using a purposive sampling technique with muzzaki criteria, Cipondoh District, Tangerang City, who were already working or had income. The results showed that each variable, namely the technology acceptance model (X1), digital literacy (X3) and trust (Z) had a positive and significant effect on the muzzaki's decision to pay zakat online (Y) with a t-count value of 2,637 p-value. 0.009>0.05, t-count 2.288 p-value 0.023>0.05, and t-count 6.278 p-value 0.000>0.05. While promotion (X2) has no significant effect on the decision of muzzaki to pay zakat online with a t-count value of 0.341 p-values 0.733 <0.05